Enhancing sepsis therapy: the evolving role of enteral nutrition - Xu, Fuchao; Lu, Geng; Wang, Jun (Frontiers in Nutrition, 2024)
Sepsis is a life-threatening organ dysfunction syndrome caused by a dysregulated response to infection in the body. Effective treatment of sepsis poses a significant challenge in today's clinical field. In recent years, enteral nutrition has garnered significant attention as an essential supportive therapeutic strategy. Serving as a means to provide ample nutritional support directly through the gastrointestinal tract, enteral nutrition not only addresses the nutritional depletion caused by the disease but also holds potential advantages in regulating immune function, maintaining intestinal mucosal barrier integrity, and promoting tissue repair. This article delves into the latest advancements of enteral nutrition in the treatment of sepsis, with a particular focus on its application effectiveness in clinical practice, potential mechanisms, and challenges faced. By examining relevant basic and clinical research, the aim is to provide a deeper understanding of nutritional therapy for sepsis patients and offer valuable insights for future research and clinical practice.